Antioxidant, Anti-inflammatory Activities and Polyphenol Profile of Rhamnus prinoides - Gui-Lin Chen; Fredrick Munyao Mutie; Yong-Bing Xu; Flora Didii Saleri; Guang-Wan Hu; Ming-Quan Guo (MDPI AG, 2020)
Rhamnus prinoides L’Herit (R. prinoides) has long been widely consumed as folk medicine in Kenya and other Africa countries. Previous studies indicated that polyphenols were abundant in genus Rhamnus and exhibited outstanding antioxidant and anti-inflammatory activities. However, there are very few studies on such pharmacological activities and the polyphenol profile of this plant up to now. In the present study, the antioxidant activities of the crude R. prinoides extracts (CRE) and the semi-purified R. prinoides extracts (SPRE) of polyphenol enriched fractions were evaluated to show the strong radical scavenging effects against 1,1-diphenyl-2- picrylhydrazyl radical 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH) (0.510 ± 0.046 and 0.204 ± 0.005, mg/mL), and 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) (0.596 ± 0.005 and 0.096 ± 0.004, mg/mL), respectively. Later, the SPRE with higher contents of polyphenols and flavonoids displayed obvious anti-inflammatory activities through reducing the NO production at the dosage of 11.11 - 100 μg/mL, and the COX-2 inhibitory activity with an IC50 value at 20.61 ± 0.13 μg/mL. Meanwhile, the HPLC-UV/ESI-MS/MS analysis of polyphenol profile of R. prinoides revealed that flavonoids and their glycosides were the major ingredients, and potentially responsible for its strong antioxidant and anti-inflammatory activities. For the first time, the present study comprehensively demonstrated the chemical profile of R. prinoides, as well as noteworthy antioxidant and anti-inflammatory activities, which confirmed that R. prinoides is a good natural source of polyphenols and flavonoids, and provided valuable information on this medicinal plant as folk medicine and with good potential for future healthcare practice.